PALATAL RUGAE AND LIP PRINT PATTERN STUDY AS THE ALTERNATIVE METHOD OF MASS NATURE DISASTER VICTIM IDENTIFICATION (Proceedings of the International Conference on Public Health, 2019)
The most common method of forensic identification is dental, fingerprint, and DNA. However those have a limitation such as high price , and limited cases. Palatal fold (rugae) and lip print pattern are a unique, stable and resistant morphological landmark foridentification. The purpose of this study is to examine the characteristic of rugae palatina and lip print pattern and the resemblance to the Minangkabau family relationship. This cross-sectional study, in 27 pure blood Minangkabaunese families. The sample was taken randomly. Palatal rugae was extracted from alginate printing. Lip print was taken on white paper after lips colored with red lipstick. IBM SPSS 17 is used for statistical analysis. The results show that there is similarity of rugae palatina based on family relationship. The circular male rugae has similarities to that of the father (p
Keywords: palatal rugae; lip print pattern; odontology forensic